Effect of dietary Bokashi supplementation on the performance of colour broiler chicken - Zakaria, Mazlinda (2016)
A study was conducted to evaluate the effect of the effective microorganisms (EM) in the feed on the performance of colour broiler chickens. EM Bokashi is the dry form product of fermented rice bran with effective microorganism (EM) activated solution. Factorial design was used in this experiment. Ninety unsexed colour broiler chicken day-old chicks were randomly allocated into three experimental treatments. Chickens were fed with three different dietary treatments. It consists of treatment 1 (0% EM Bokashi, but with 2% untreated rice bran) as control, treatment 2 (2% EM Bokashi) and treatment 3 (4% EM Bokashi) in the feed. Each treatment had three replicates and five birds per cage. Twenty one days old chicks were separated between female and male and grouped randomly according to their sex after they were with commercial starter feed from day old and water ad libitum. Broiler starter ration was continued until day 35. Day old chickens, and grower ration was fed from 36 days to 63 days of age. The EM Bokashi was added into the respective ration starting from day 21-days old chicks. The amount of feed consumption was recorded daily. Weekly body weight of the chicks was also recorded. From the data, average feed consumption, average body weight, weight gain and feed conversion ratio (FCR) were calculated. The results suggested that the weight gain and feed conversion ratio (FCR) were significantly different between treatments. There was significantly better differences (P<0.05) in average body weight among the treatments. Average feed intake of chicken was significantly inferior difference among the three treatments. Average weekly weight gain of chicken in T3 have slightly significant differences (P<0.05) among the treatments. There was significantly higher differences (P<0.05) on average feed conversion ratios (FCR) among the treatments. In conclusion, feeding different level of Bokashi give will improve the body weight, body weight gain, feed intake and feed convention ratio.